Comparison of anterior segment parameters in patients with pseudoexfoliation glaucoma, patients with pseudoexfoliation syndrome, and normal subjects - Kaygisiz,Mehmet (2018)
ABSTRACT Purpose: To compare the anterior segment parameters of patients with pseudoexfoliation syndrome, patients with pseudoexfoliation glaucoma, and normal subjects. Methods: This prospective, controlled, comparative study included 150 eyes of 150 patients. The patients were divided into the pseudoexfoliation syndrome group, the pseudoexfoliation glaucoma group, and the control group (50 patients in each group). Axial length, central corneal thickness, aqueous depth, anterior chamber depth, lens thickness, K1 and K2 keratometry values, and white to white distance measurements were obtained by optical biometry and compared between the groups. Results: The mean ages of the pseudoexfoliation syndrome, pseudoexfoliation glaucoma, and control patients were 62.18 ± 6.21, 61.80 ± 6.62, and 59.40 ± 6.89 years, respectively. There were no statistically significant differences between the groups in mean age or sex ratio (p>0.05). Mean central corneal thickness was statistically significantly greater, mean aqueous depth and anterior chamber depth were statistically significantly greater, and mean lens thickness was statistically significantly less in the control group than in the pseudoexfoliation syndrome and pseudoexfoliation glaucoma groups (p<0.05). Pairwise comparisons of the pseudoexfoliation syndrome group and the pseudoexfoliation glaucoma group revealed that there were no significant differences between these two groups in central corneal thickness, aqueous depth, anterior chamber depth, and lens thickness (p>0.017). Conclusions: Patients with pseudoexfoliation glaucoma and pseudoexfoliation syndrome had greater lens thickness, shallower aqueous depth and anterior chamber depth, and less central corneal thickness than normal subjects. None of the anterior segment parameters differed between patients with pseudoexfoliation syndrome and patients with pseudoexfoliation glaucoma.